Media representation of armed conflicts in North Kivu: critical analysis of local and international narratives - Hilaire AGANZE MAHESHE, (IJRDO - Journal of Social Science and Humanities Research, 2025)
This article examines the media representation of armed conflicts in North Kivu by analyzing both local and international narratives. Using a critical approach, it identifies the convergences, divergences, and structural biases that shape these narratives. Local narratives, while deeply rooted in community realities, are often constrained by political pressures and material limitations. International narratives, on the other hand, enjoy broader dissemination but tend to oversimplify the complex dynamics of the conflict. The analysis reveals that these narratives, though complementary, exhibit tensions that influence global and local perceptions of the conflicts, as well as political and humanitarian responses. The article advocates for strengthening local media, fostering greater collaboration between local and international journalists, and improving the contextualization of narratives to enhance the understanding and management of conflicts in the region.